Analisis Peran E-commerce Terhadap Perilaku Konsumtif Remaja - Aisyah, Siti Nur; Muchbichin, Muchbichin; Sa'diyah, Halimatus; Anggraini, Lulus Dwi; Mawaddah, Nuril Vina; Firmansyah, Aditya (JoEMS (Journal of Education and Management Studies), 2023)
Information technology is an important factor that brings about changes in shopping culture in Indonesia, namely from conventional shopping culture to modern shopping through e-commerce. The existence of e-commerce provides a new sensation in shopping, where sellers and buyers do not have to meet face to face in making transactions so that it saves time, money and effort, and contributes significantly to the growth of businesses and consumers. The purpose of this study was to determine the role of e-commerce on adolescent behavior. This research was conducted from 18 December 2022 to 1 January 2023 using a survey method. The sample used in this study were 72 adolescents aged 15 to 19 years. The results showed that the respondents did not experience online shopping addiction. This can be seen from the frequency of e-commerce access, which is generally 1-2 times per day (69.4%). Spending on e-commerce, Rp. 100,000 per month (37.5%), and the most commonly used e-commerce application is shopee (81.9%).